Appropriateness to set a group health‐based guidance value for fumonisins and their modified forms. (23rd February 2018) - ,; Knutsen, Helle‐Katrine; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); et al.
Abstract: The EFSA Panel on Contaminants in the Food Chain (CONTAM) established a tolerable daily intake (TDI) for fumonisin B1 (FB1 ) of 1.0 μg/kg body weight (bw) per day based on increased incidence of megalocytic hepatocytes found in a chronic study with mice. The CONTAM Panel considered the limited data available on toxicity and mode of action and structural similarities of FB2–6 and found it appropriate to include FB2, FB3 and FB4 in a group TDI with FB1 . Modified forms of FBs are phase I and phase II metabolites formed in fungi, infested plants or farm animals. Modified forms also arise from food or feed processing, and include covalent adducts with matrix constituents. Non‐covalently bound forms are not considered as modified forms. Modified forms of FBs identified are hydrolysed FB1–4 (HFB1–4 ), partially hydrolysed FB1–2 (pHFB1–2 ), N ‐(carboxymethyl)‐FB1–3 (NCM‐FB1–3 ), N ‐(1‐deoxy‐d ‐fructos‐1‐yl)‐FB1 (NDF‐FB1 ), O ‐fatty acyl FB1, N ‐fatty acyl FB1 and N ‐palmitoyl‐HFB1 . HFB1, pHFB1, NCM‐FB1 and NDF‐FB1 show a similar toxicological profile but are less potent than FB1 . Although in vitro data shows that N ‐fatty acyl FBs are more toxic in vitro than FB1, no in vivo data were available for N ‐fatty acyl FBs and O ‐fatty acyl FBs. The CONTAM Panel concluded that it was not appropriate to include modified FBs in the group TDI for FB1–4 . The uncertainty associated with the present assessment is high, but could be reduced provided more data are made available on occurrence, toxicokinetics and toxicity of FB2–6 and modified forms of FB1–4 . Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1148/full